PELAKSANAAN FUNGSI BADAN PERMUSYAWARATAN DESA DALAM MENAMPUNG DAN MENYALURKAN ASPIRASI MASYARAKAT DI DESA WAIJARANG KECAMATAN NUBATUKAN KABUPATEN LEMBATA DITINJAU DARI UNDANG-UNDANG NOMOR 6 TAHUN 2014 - Karang, Mariani Ngura; Tuba Helan, Yohanes G; Lamataro, Cyrilius W. T (Petitum Law Journal, 2023)
The lack of knowledge of the Village Consultative Body regarding the function of accommodating and channeling community aspirations in Waijarang Village, Nubatukan District, Lembata Regency and the lack of awareness of the Village Consultative Body regarding the function of accommodating and channeling community aspirations so that the Village Consultative Body does not involve the community in terms of accommodating and channeling community aspirations and the community is lacking active participation channeling aspirations. The research approaches used in this research are a legislative approach, a conceptual approach, and a legal sociological approach (socio legal). The data collection techniques used were interviews and literature study techniques/documents studied and based on literature related to this research and the provisions of applicable laws and regulations. The results of the research show: (1) The implementation of the function of the Village Consultative Body in accommodating and channeling the aspirations of the community in Waijarang village, Nubatukan District, Lembata Regency is not running effectively due to a lack of understanding and awareness from the Village Consultative Body. (2) External inhibiting factors in implementing the function of the Village Consultative Body in carrying out its function of accommodating and channeling community aspirations, namely that the community does not understand the function of the Village Consultative Body and the community does not participate actively in channeling aspirations through the Village Consultative Body.